2018
DOI: 10.1101/440164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the dynamics of signaling events in the BMP, WNT, and NODAL cascade during self-organized fate patterning in human gastruloids

Abstract: During gastrulation, the pluripotent epiblast is patterned into the three germ layers, which form the embryo proper. This patterning requires a signaling cascade involving the BMP, WNT and NODAL pathways; however, how these pathways regulate one another in space and time to generate cell-fate patterns remains unknown. Using a human gastruloid model, we show that BMP signaling initiates a wave of WNT signaling, which, in turn, initiates a wave of NODAL signaling. While WNT propagation depends on continuous BMP … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 47 publications
(71 reference statements)
5
38
1
1
Order By: Relevance
“…11,12 Similarly, PSC proliferation and differentiation recapitulate embryonic tissue development and are accompanied by dynamic remodeling of ECMs and local gradients of morphogens. [13][14][15] Hence, ECM proteins and regulatory factors surrounding stem cells form a regulatory niche and play essential roles in modulating stem cell fate. 16,17 Understanding and recapitulating the characteristics of stem cell microenvironment should significantly improve our ability to control stem cell fate in tissue regeneration and cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Similarly, PSC proliferation and differentiation recapitulate embryonic tissue development and are accompanied by dynamic remodeling of ECMs and local gradients of morphogens. [13][14][15] Hence, ECM proteins and regulatory factors surrounding stem cells form a regulatory niche and play essential roles in modulating stem cell fate. 16,17 Understanding and recapitulating the characteristics of stem cell microenvironment should significantly improve our ability to control stem cell fate in tissue regeneration and cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Models that have previously tried to explain the emergence of germ-layer patterns have relied on gradients of individual signals including BMP4 (Etoc et al, 2016;Tewary et al, 2017), NODAL (Tewary et al, 2019), and WNT (Chhabra et al, 2019). We build on these models in three ways.…”
Section: Discussionmentioning
confidence: 99%
“…As we intended to create a minimal GRN that captured both the maintenance of pluripotency and exit to germ-layer states, we focused on a narrow set of genes, signals, and interactions for model development. For example, we set-aside NANOG due to its lineage restricted role in maintaining pluripotency (Wang et al, 2012) and NODAL signalling given that BMP & WNT pathways have been shown to successfully trigger exit from pluripotency to germ-layer fates (Tewary et al, 2017;Chhabra et al, 2019;Martyn et al, 2018). Similarly, other germ-layer fate associated TFs, such as EOMES, FOXA1, OTX2, were also not directly considered at this time.…”
Section: A Minimal Grn Captures Exit From Pluripotency To Germ-layer mentioning
confidence: 99%
See 1 more Smart Citation
“…The BMP, WNT and NODAL signaling cascade is important during mammalian gastrulation and gastruloid formation in micropattern (Chhabra et al, 2018;Martyn et al, 2018). Specifically, WNT and NODAL pathways synergize to instruct mesoderm differentiation in gastruloids, whereas changes in the duration of BMP signaling alter the position of mesodermal ring (Chhabra et al, 2018). Thus, the dynamic interplay of signaling pathways, such as the duration and timing, governs cell fate patterns in gastruloids.…”
Section: Discussionmentioning
confidence: 99%